2019
DOI: 10.1007/s12576-019-00723-3
|View full text |Cite
|
Sign up to set email alerts
|

Endurance running exercise is an effective alternative to estradiol replacement for restoring hyperglycemia through TBC1D1/GLUT4 pathway in skeletal muscle of ovariectomized rats

Abstract: Menopause is a risk factor for impaired glucose metabolism. Alternative treatment of estrogen for postmenopausal women is required. The present study was designed to investigate the effects of 5-week endurance running exercise (Ex) by treadmill on hyperglycemia and signal pathway components mediating glucose transport in ovariectomized (OVX) placebo-treated rats, compared with 4-week 17β-estradiol (E2) replacement or pair-feeding (PF) to the E2 group. Ex improved the hyperglycemia and insulin resistance index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Exercised rats muscle (soleus and epitrochlearis) did not show significant change in Tbc1d4 expression [21]. 17β-oestradiol enhanced the expression of Tbc1d4 mRNA in ovariectomized rats gastrocnemius muscle, but not in mesenteric adipose tissue [28]. Murine Tbc1d4 expression was markedly down-regulated in skeletal muscles with age [27], TBC1D4 expression in human cumulus cells showed opposite relation [34].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Exercised rats muscle (soleus and epitrochlearis) did not show significant change in Tbc1d4 expression [21]. 17β-oestradiol enhanced the expression of Tbc1d4 mRNA in ovariectomized rats gastrocnemius muscle, but not in mesenteric adipose tissue [28]. Murine Tbc1d4 expression was markedly down-regulated in skeletal muscles with age [27], TBC1D4 expression in human cumulus cells showed opposite relation [34].…”
Section: Discussionmentioning
confidence: 93%
“…We have observed no significant effect of adipokines and myokines on both genes expression in cultured human subcutaneous adipocytes. Plethora of methods was used to determine the abundance of TBC1D1 and TBC1D4 on protein and mRNA level, including Western blotting [16,19,20,21,22,23,24,25,12,26,27,28,11,29,14], Reverse Transcription PCR (RT-PCR) [22], quantitative PCR (qPCR) [23,20,30,31,12,26,27,32,28,33,14], microarray [20] and RNA sequencing (RNA-seq) with qPCR validation [34,13,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To directly assess the anorexigenic effect of E2 replacement on glucose homeostasis, a pair‐fed group would be included in our experiments. Our previous study, which used NCD‐fed rats, showed that food restriction by pair‐feeding to E2 replacement group in the PL group ameliorated hyperglycemia in the OVX rats but failed to mimic the effects of E2 replacement on basal levels of insulin signaling components, Akt2 and AS160 (Kawakami et al, 2019). This finding supports direct E2 action of the signaling pathway instead of anorexia‐induced indirect action.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise intervention seems to be more effective in regulating GLUT4 signal in muscle tissue. Many studies [34][35][36] have found that exercise can up-regulate insulin signal and increase the expression and translocation of GLUT4 in muscle tissue. In follow-up studies, calorie restriction combined with exercise intervention can be considered to enhance the intervention effect.…”
Section: Discussionmentioning
confidence: 99%